Drug-eluting stents: a critique. Issue 2 (14th January 2008) - Melikian, N; Wijns, W
Abstract : Despite advances in the design of balloons and stents, restenosis remains a major drawback of coronary angioplasty. Multiple randomised trials have demonstrated that drug-eluting stents (DES) can significantly reduce rates of restenosis by 60–75% across both lesion and patient subsets. In recent years there has been an exponential increase in the worldwide use of DES. This expansion has occurred as a result of an enthusiastic extrapolation of results from randomised trials leading to "off-label" use of DES in anatomical or clinical high-risk scenarios, or both. However, emerging medium- to long-term follow-up data have raised concerns about the safety of DES. A number of analyses have recently shown increased rates of late stent thrombosis in patients with DES. The exact mechanisms leading to stent thrombosis remain unclear. This article critically reviews the available efficacy and safety data on DES and discusses the factors influencing our current practice and perception of the net value of DES.